ANALYSIS OF MONITORING AND MANAGEMENT METHODS FOR ENERGY SUPPLY SOURCES (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
Efficient energy management is a crucial factor in the operation of a system. Today, many systems cannot effectively function without an uninterrupted power supply. Ensuring the continuity and reliability of electrical energy is essential in monitoring, analyzing, and managing energy consumption. By continuously monitoring energy supply sources and improving automatic control methods, it is possible to enhance energy efficiency and ensure uninterrupted power supply. Therefore, this research analyzes the methods of monitoring and managing electrical energy supply sources.
Keywords: uninterrupted electrical energy; sensors; IoT; microcontroller